Preparation of Floating Gel Beads and Study on Their Performance in Degrading Fluoroquinolone Antibiotics - Malfait, Zahra; Schowald, Hashna (Journal of Green Energy and Environmental Engineering, 2024)
Antibiotics, as typical emerging pollutants, originated from metabolites produced by microorganisms in nature to compete for survival resources, which can inhibit or kill other microorganisms. Long-term abuse of antibiotics can lead to the rapid spread of bacterial resistance genes (ARGs) and even the emergence of "superbugs," rendering traditional antibiotics ineffective and thus posing serious environmental pollution and ecological risks. Among various treatment technologies, photocatalytic technology is a green, efficient, and highly promising method for water pollution remediation. Therefore, this study constructed a heterojunction and established a floating catalytic system to prepare photocatalytic gel beads (CA/CNF@BiOBr/Ti₃C₂) with a hollow porous structure, which simultaneously possesses favorable mass transfer properties and effective catalytic active centers. These gel beads can mineralize various fluoroquinolone antibiotics (FQs) and exhibit resistance to interference from complex water environments, along with excellent stability. The specific research results are as follows: (1) CA/CNF@BiOBr/Ti₃C₂ photo-active gel beads assembled successfully.(2) Embedding Ti₃C₂ widened the light-harvesting window and forged a BiOBr/Ti₃C₂ Schottky junction that accelerates charge parting, drives carriers outward, and trims interfacial resistance.The junction boosts the gel bead’s photoelectrochemical output, turning more photons into usable current.(3) How O₂ shuttle and the self-generated electric field amplify each other inside the bead.Electrons hop from BiOBr to Ti₃C₂, sketching an internal field that tilts BiOBr’s bands upward and blocks the U-turn of light-sparked electrons. On the other hand, the CA/CNF@BiOBr/Ti₃C₂ gel beads in the three-phase system can directly contact O₂ in the air and reduce its diffusion distance, thereby achieving rapid O₂ transport and sufficient supply. A steady O₂ feed devours the migrated electrons, stifling charge recombination and fueling a burst of ·O₂⁻ and ·OH radicals.Ultimately, these highly oxidative ROS oxidize and decompose MOX molecules into CO₂, H₂O, and less toxic small molecules.